2014
DOI: 10.1103/physrevb.89.155429
|View full text |Cite
|
Sign up to set email alerts
|

Valley polarization in magnetically doped single-layer transition-metal dichalcogenides

Abstract: We demonstrate that valley polarization can be induced and controlled in semiconducting single-layer transition-metal dichalcogenides by magnetic doping, which is important for spintronics, valleytronics, and photonics devices. As an example, we investigate Mn-doped MoS 2 by first-principles calculations. We study how the valley polarization depends on the strength of the spin orbit coupling and the exchange interaction and discuss how it can be controlled by magnetic doping. Valley polarization by magnetic do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
126
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(129 citation statements)
references
References 48 publications
2
126
0
1
Order By: Relevance
“…Actually, 2D MoS 2 ferromagnetic (FM) materials have been heralded as ideal candidates for the dilute magnetic semiconductors, which can exploit both the charge and spin degrees of freedom of the electron in one device [18], yielding remarkable properties and functionalities, in the field of spintronics. Besides the various magnetic properties induced by doping transition-metal [8][9][10][11][12][13]19,20], the adsorption of adatoms at the 2D monolayer MoS 2 have crucial effects on the electronic and magnetic properties [21,22]. The large spatial extensions of spin density and long-range antiferromagnetic (AFM) coupling were observed in H-and F-absorbed MoS 2 monolayers.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Actually, 2D MoS 2 ferromagnetic (FM) materials have been heralded as ideal candidates for the dilute magnetic semiconductors, which can exploit both the charge and spin degrees of freedom of the electron in one device [18], yielding remarkable properties and functionalities, in the field of spintronics. Besides the various magnetic properties induced by doping transition-metal [8][9][10][11][12][13]19,20], the adsorption of adatoms at the 2D monolayer MoS 2 have crucial effects on the electronic and magnetic properties [21,22]. The large spatial extensions of spin density and long-range antiferromagnetic (AFM) coupling were observed in H-and F-absorbed MoS 2 monolayers.…”
Section: Introductionmentioning
confidence: 97%
“…Since the successful cleavage of a monolayer molybdenum disulfide (MoS 2 ) from its three-dimensional (3D) bulk counterpart [1], massive research efforts also have been focused on the two-dimensional (2D) atomic crystals MoS 2 due to their great potential in applications, deriving from the optical [2], electronic [3,4], mechanical [5], and catalytic properties [6] of the materials. More recently, it has been demonstrated that valley polarization can be induced and controlled by using a circularly polarized light or by a magnetically doping in single-layer MoS 2 [7,8]. Diverse magnetic orderings have been reported recently in transition-metal-doped including Mn, Fe, Cu-doped MoS 2 [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 97%
“…When the applied external fields including force, electric, magnetic or optical ones are removed, the system recovers to the initial paravalley state. For the purpose of applying in next-generation electronic products with nonvolatility, scheme by means of magnetic doping2324252627 appeared as an alternative approach. In consideration of the electronic transports suffering from impurity scattering, a more intelligent way using the magnetic proximity effect2829 is proposed very recently.…”
mentioning
confidence: 99%
“…One major challenge to observe the rapid G CAR oscillation is the fabrication of a high-quality sample as the interface roughness and Fermi level fluctuations can wash out the oscillation. Finally, we point out that the pCAR mechanism proposed here is universally applicable to systems with similar band topology such as YiG-graphene [43] and monolayer transition-metal dichalcogenides with magnetic doping [44] or with proximity to EuO [45]. These structures offer alternative platforms to test the validity of our prediction.…”
mentioning
confidence: 64%